Protective Effectiveness of an Immunization Protocol Against the Toxic Effects of Loxosceles intermedia Venom in Rabbits - de Miranda, Ana Luísa Soares; Lima, Sabrina de Almeida; Botelho, Ana Flávia Machado; Gomes Campos, Marco Túlio; Eckstein, Camila; Minozzo, João Carlos; Chávez-Olórtegui, Carlos Delfin; Soto-Blanco, Benito (Frontiers in Veterinary Science, 2022)
Loxosceles spp. (brown spiders) bites are responsible for the development of a syndrome consisting mainly of dermonecrotic lesions, and also systemic effects. Rabbits are one of the main experimental models used for better understanding the systemic and local effects of Loxosceles venom. The aim of this study is to evaluate the toxic and protective effects of rabbits immunized with Loxosceles spp. venom. Male New Zealand rabbits were allocated as a control group (CG; n = 5) that received adjuvant (Montanide) and phosphate-buffer saline (PBS), or as venom group (VG; n = 5) that received 21 μg of Loxosceles venom using Montanide as adjuvant. After five immunization cycles, a trial with 7 μg of Loxosceles intermedia (L. intermedia) venom was performed, and dermonecrotic lesions were measured. The rabbits were then euthanized, and their organs were collected for histopathology analysis. Rabbits that had undergone Loxosceles venom immunization protocol showed minor clinical disturbances during the experimental period. The used immunization protocol protected the rabbits against the toxic effect of the Loxosceles venom because they showed minor clinical disturbances during the experimental period.